Personalised Medicine: The Rising Sun - Desai, Chandani T.; Shah, Gaurav S. (International Journal of Applied Sciences and Biotechnology, 2015)
Inter individual genetic variation contributes to both disease susceptibility and response to drugs. The genetic makeup of every individual isdistinctive, henceforth there are variations in the gene products. It is also responsible for the phenotypic diversity, which results in the differentcapacity of each individual to respond to exogenous substances, such as drugs and xenobiotics, and in the different propensity to induceundesirable health effects. So, the aim of personalised medicine is to increase the possibility of therapeutic efficiency and to decrease the drugtoxicity risk for an individual patient. Int J Appl Sci Biotechnol, Vol 3(2): 139-142 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12545